Removal of Dyes From Textile Industry Using Cellulose Nanowhiskers From Acacia Mangium - Abdul Hamid, Nor Hazren; A., Farahah; Ali, R.; Mohamed Sunar, Norshuhaila (Penerbit UTHM, 2020)
There are more than 10,000 commercially available dyes with over 7 × 105 tonnes of dye stuff produced annually. It is estimated that 2 % of dyes produced annually is discharged in effluents from associated industries. Among various industries, textile industry ranks first in usage of dyes for coloration of fiber. The total dye consumption of the textile industry worldwide is in excess of 107 kg/year and an estimated 90 % of this ends up on fabrics [1]. The discharged of colored effluent impose negative result for both toxicological and esthetical reasons. Dyes which are chemically and photolytically stable are highly persistent in natural environment. Wastewater treatment in textile and dye industry mainly involved in treatment of highly colored wastewater containing variety of dyes in different concentrations. The wastewater needs to be treated prior to discharge by removing dye color in order to protect environment and as per the statutory guidelines.